Stock returns and liquidity after listing switch on the Warsaw Stock Exchange - Podedworna-Tarnowska, Dorota; Kaszyński, Daniel (Economics and Business Review, 2022)
The aim of the article is to evaluate the market reaction to the change of listing venue of companies moving from the alternative market to the regulated market of the Warsaw Stock Exchange. To do so, we investigated 71 switches, and their effect on market returns and liquidity. While the transfer itself creates a negative market reaction, the announcement of the transfer of a company and the institutional confirmation by the supervision of the company’s readiness for this transfer resulting from the approval of the prospectus creates positive market reactions. As a result of the transfer of companies there is an improvement in the liquidity of the shares. The empirical findings of the study could assist managers and investors in understanding the impact of stock exchange migration on returns and the liquidity of shares in the shorter and longer term.